2000
DOI: 10.1038/35019025
|View full text |Cite
|
Sign up to set email alerts
|

Controlled surface charging as a depth-profiling probe for mesoscopic layers

Abstract: Probing the structure of material layers just a few nanometres thick requires analytical techniques with high depth sensitivity. X-ray photoelectron spectroscopy (XPS) provides one such method, but obtaining vertically resolved structural information from the raw data is not straightforward. There are several XPS depth-profiling methods, including ion etching, angle-resolved XPS (ref. 2) and Tougaard's approach, but all suffer various limitations. Here we report a simple, non-destructive XPS depth-profiling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
160
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(165 citation statements)
references
References 14 publications
4
160
1
Order By: Relevance
“…The base pressure in the analysis chamber was kept below 10 −9 Torr. CSC 23,24 was used in order to differentiate between sample domains, as well as to eliminate signals originated from the underlying adhesive tape (see SI). The CSC data further provides information on the electrical properties of the resolved domains.…”
Section: Xps Measurementsmentioning
confidence: 99%
“…The base pressure in the analysis chamber was kept below 10 −9 Torr. CSC 23,24 was used in order to differentiate between sample domains, as well as to eliminate signals originated from the underlying adhesive tape (see SI). The CSC data further provides information on the electrical properties of the resolved domains.…”
Section: Xps Measurementsmentioning
confidence: 99%
“…Elegant use of surface charging for lateral differentiation of mesoscopic layers and for depth profiling in 1-10 nm thin layers have recently been reported. 31,32 In most of these studies, surface charging was controlled/varied via a low energy electron flood gun. In a recent report, Havercroft and Sherwood 33 demonstrated that simple external biasing of the sample holder by a d.c. power supply can also be used to induce differential surface charging.…”
Section: Introductionmentioning
confidence: 99%
“…This negative charging, dubbed as controlled surface charging, has been utilized for deriving some chemical/physical parameters of surface structures. [3][4][5][6] Otherwise, the emphasis, until now, has mostly been on recording the line positions in XPS, and except for very few cases, [7][8][9][10][11] no attempts for electrical measurements have been made. The total current is the sum of two opposing currents, resulting from photoelectrons, and secondary electrons going out of the sample, and stray electrons or electrons from the flood gun, going into the sample, which can easily be controlled by application of a small ͑0-10 V͒ external bias, as we have reported recently.…”
mentioning
confidence: 99%